Effects of fermentation condition on production of β-glucanase and xylanase by Trichoderma reesei - GU Sai-hong; SUN Jian-yi; LI Wei-fen; XU Zi-rong (浙江大学学报. 农业与生命科学版)
The fermentation condition for efficacious production of β-glucanase and xylanase by Trichoderma reesei was studied. The results showed that the best carbon and nitrogen sources for xylanase production were lactose combined with beef extract. On the other hand, for β-glucanase production combination of wheat bran and ammonium sulphate was most successful. The optimal initial pH and fermentation condition was 4.0 at 30℃ for xylanase production and 5.0 at 30℃ for β-glucanase production. In addition, Toween 20, Toween 80 and betaine were found to increase yields of xylanase and β-glucanase, the optimal stimulator being betaine for xylanase production and Toween 20 for β-glucanase production.. Based on course of β-glucanase and xylanase by T. reesei, the initiation of xylanase and β-glucanase production were at 20 h and 24 h, respectively, while the peak time for their production were at 48h and 44h, respectively.